Kun-Dan Decoction Ameliorates Insulin Resistance by Activating AMPK/mTOR-Mediated Autophagy in High-Fat Diet-Fed Rats - Su, Zuqing; Zeng, Kexue; Feng, Bing; Tang, Lipeng; Sun, Chaoyue; Wang, Xieqi; Li, Caiyun; Zheng, Guangjuan; Zhu, Ying (Frontiers in Pharmacology, 2021)
Background: Metabolic syndrome is characterized by central obesity, hyperglycemia and hyperlipidemia. Insulin resistance is the leading risk factor for metabolic syndrome. Kun-Dan decoction (KD), a traditional Chinese medicine, has been applied to treat patients with metabolic syndrome for over ten years. It is increasingly recognized that autophagy deficiency is the key cause of metabolic syndrome. Therefore, we aimed to explore whether KD can activate autophagy to improve metabolic syndrome. Methods: Network pharmacology was used to explore the underlying mechanism of KD in the treatment of metabolic syndrome. The high-fat diet-fed rats and oleic acid-induced LO2 cells were employed in our study. Oral glucose tolerance test and insulin tolerance test, obesity and histological examination, serum cholesterol, triglyceride, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), homeostasis model assessment of insulin resistance (HOMA-IR) and insulin sensitivity in high-fat diet-fed rats were analyzed. Furthermore, the protein expressions of adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK), phospho-AMPK, mammalian target of rapamycin (mTOR), phospho-mTOR, p62, autophagy related protein (Atg) 5, Atg7, Atg12, Atg13, Atg16L1 and microtubule-associated protein 1A/1B-light chain 3 (LC3)-Ⅱ/Ⅰ were examined in rats and LO2 cells. Moreover, autophagy activator rapamycin and inhibitor 3-methyladenine, and small interfering RNA against Atg7 were utilized to verify the role of autophagy in the treatment of metabolic syndrome by KD in oleic acid-induced LO2 cells. Results: Results from network pharmacology indicated that targeted insulin resistance might be the critical mechanism of KD in the treatment of metabolic syndrome. We found that KD significantly suppressed obesity, serum cholesterol, triglyceride and LDL-C levels and increased serum HDL-C level in high-fat diet-fed rats. Furthermore, KD enhanced insulin sensitivity and attenuated HOMA-IR in high-fat diet-fed rats. Western blot showed that KD could enhance autophagy to increase the insulin sensitivity of high-fat diet-fed rats and oleic acid-induced LO2 cells. Furthermore, 3-methyladenine and small interfering RNA against Atg7 could reverse the protective effect of KD on LO2 cells. However, rapamycin could cooperate with KD to enhance autophagic activation to increase insulin sensitivity in LO2 cells. Conclusion: The induction of autophagy may be the major mechanism for KD to improve insulin resistance and metabolic syndrome.